2017
DOI: 10.1136/jmedgenet-2017-104891
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-genotype correlations in Leigh syndrome: new insights from a multicentre study of 96 patients

Abstract: Our study provides new insights into phenotype-genotype correlations in Leigh syndrome and particularly in patients with complex I deficiency and with defects in the mitochondrial ATP synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 34 publications
7
72
4
Order By: Relevance
“…In the present study, the genetic complexity of 17 different nuclear and mitochondrial genes was identified. Genetic defects associated with complex I deficiency were the most frequent, with a total diagnostic yield of 64.5% (40/62 families) . These included six mitochondrial genes in 18 families, including MTATP6 , MTND3 , MTND6 , MTND5 , MTND1 , and MTTK , in descending order of frequency.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the genetic complexity of 17 different nuclear and mitochondrial genes was identified. Genetic defects associated with complex I deficiency were the most frequent, with a total diagnostic yield of 64.5% (40/62 families) . These included six mitochondrial genes in 18 families, including MTATP6 , MTND3 , MTND6 , MTND5 , MTND1 , and MTTK , in descending order of frequency.…”
Section: Discussionsupporting
confidence: 92%
“…To date, few large cohort studies of genotype‐phenotype correlations have been conducted . Unlike the patients in a previous study, those in ours with mutations in MTND and NDUF did not show a higher incidence of cardiac or ocular involvement . In addition, neither the cerebral cortex nor the kidney appeared to be more frequently affected in patients with NDUF mutations compared with the other mutation‐positive cases .…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations